Clinical and laboratory presentation of classical galactosaemia in infants and children at Chris Hani Baragwanath Academic hospital - Monareng, Mohamed (My University, 2017)
Background. Classical Galactosaemia is an autosomal recessive disorder of galactose metabolism due to a deficiency of galactose-1-phosphate uridyltransferase (GALT) enzyme. In the neonatal period it can be a life threatening disease with multi organ involvement and non-specific symptoms and signs. In infancy and childhood, it can present with cataracts and cirrhosis. Long-term complications include verbal dyspraxia, cognitive disability and hypergonadotrophic hypogonadism. Galactosaemia responds to a galactose free diet and early diagnosis reduces morbidity and mortality, especially in early infancy. Objectives. To determine the number of cases with classical galactosaemia seen at Chris Hani Baragwanath Academic Hospital (CHBAH) Paediatric Gastroenterology, Hepatology and Nutrition Unit (PGHNU) Soweto Gauteng, between January 1994 and December 2013 and to document the clinical, laboratory characteristics and outcome of these patients. Methods. All children diagnosed at PGHNU with classical galactosaemia between January 1994 and December 2013 were included in the study. Clinical and laboratory parameters were determined and analysed. Outcome and long-term complications were documented. Results. Twenty-three children with classical galactosaemia were diagnosed during the study period. All patients had severely low or absent GALT enzyme activity. Mean age at diagnosis was 4.6 months (age range 3 -24 months). The commonest presenting symptoms were yellow discolouration of the eyes (74%), abdominal distension (65%) and failure to gain weight (57%). Most frequent clinical features at diagnosis were hepatomegaly (100%), pallor (78%), jaundice (78%), ascites (61%) failure to thrive (52%) and cataracts (55%). Laboratory findings included metabolic acidosis (78%), coagulopathy (65%) and liver derangements (61%). Anaemia was noted in 78% of the patients, which was primarily macrocytic. Eight out of the 23 patients presented with evidence of infection. Long-term complications in those assessed, included visual problems (12/18patients), developmental delay(9/16patients) and speech impairment (4/9patients). Conclusion. The study provides information on the clinical, haematological and biochemical presentation of galactosaemia thus increasing the awareness of the condition and encouraging strategies aimed at early recognition. This will prevent on- going damage to target organs in postnatal life. The study also documents the presence of long-term complications in the South African black child with classical galactosaemia, encouraging a structured follow up programme to prevent, identify and manage complications such as neurodevelopmental delay and speech impairement.
Keywords: Galactosemias; Infant